IMPROVING TEACHERS' ABILITY IN USING WHATSHAPP VOICE NOTE FACILITIES AS A MEDIA FOR DISTANCE LEARNING THROUGH INTEGRATED GUIDANCE ACTIVITIES AT SD BOROSUCI KAPANEWON KALIBAWANG KABUPATENKULON PROGO ACADEMIC YEAR 2020/2021 - Suprihatin Suprihatin (International Journal of Chemistry Education Research, 2021)
ABSTRACT: This study aims to determine and describe the teacher's ability to use the WhatsApp Voice Note application program in the distance learning process through integrated mentoring. The sample in this study was 9 teachers consisting of 6 classroom teachers and 3 subject teachers who were selected based on criteria using the WhatsApp Voice Note application program. This research was conducted in 2 cycles. Each cycle consists of 2 meetings and research procedures include; planning, implementation, observation and reflection. Meanwhile, to find out the teacher's activities at work, the researchers completed measuring instruments with observation instruments based on their ability to use the WhatsApp Voice Note application. The next aspect observed was the implementation of mentoring activities for researchers (principals). The results of the first cycle of research on the teacher's ability to use WhatsApp Voice Notes in Distance Learning obtained the lowest average score of the first cycle of 70.86%, the conversion value of 3, the "Good" category the highest average score of 77.55%, the conversion value; 3, category “Good”. The lowest average score in cycle II; 86.86%, value conversion; 4, “Very Good” category, the highest average score; 91.30%, value conversion; 4, “Very Good” category. As for the increase in the results of the first cycle to the second cycle; 13.75%. Furthermore, the results of the research cycle I the average score based on the percentage obtained the lowest average score of 82.04%, the conversion value was 3, the category "Satisfactory" while the highest average score reached 87.89%, the conversion value was 4, the category "Very Satisfactory" cycle II obtained the lowest average score of 89.72%, conversion value of 4, category "Very Satisfactory" the highest average score of 94.63%, conversion value of 4, category "Very Satisfactory". The results of the research cycle I and II there was an increase of 6.74%. The results of interviews with participants and researchers related to the implementation of the guidance program are contained in the interview transcript table for the WhatsApp Voice Note application program material considering that during the pandemic it was not only SD Negeri Borosuci Kalibawang that experienced difficulties, but every elementary school in the Kulon Progo Regency area. Research through integrative guidance is very helpful for teachers to add new knowledge about the WhatsApp Voice Note application. Furthermore, the principal also feels that it provides new experiences and is helped by all teachers who have a passion for learning to do distance learning in the era of the covid-19 pandemic.